Islamic Spiritual Counseling in Improving the Emotional Resilience of Broken Home Students at Muhammadiyah Middle School Tanjung Redeb - Ibnu Abbas; Khamam Khosiin; Ahsan Hakim (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe the model of Artificial Intelligence utilization in Islamic Religious Education learning and analyze its implications for student learning motivation at SMK Muhammadiyah Berau. This research used a qualitative descriptive approach with a case study design. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers, students, the principal, and the vice principal for curriculum affairs. The findings show that AI is used as a learning reference, instructional support tool, creative learning medium, evaluation aid, and independent learning assistant. AI helps students access materials more easily, understand religious concepts faster, create digital learning products, and increase their interest in learning. However, the use of AI also creates challenges, such as dependence on instant answers, weak critical thinking, limited source verification, and reduced spiritual reflection. Therefore, the role of Islamic Religious Education teachers remains central in guiding students to use AI ethically, verify religious content, and connect learning with Islamic values. This study proposes an AI-assisted Islamic Religious Education learning model based on Islamic adab, consisting of orientation, exploration, verification, dialogue, production, reflection, and evaluation. The model strengthens student motivation while preserving the moral and spiritual mission of Islamic education.